Behavioral Counseling Theory with Self-Management Techniques to Reduce Procrastination and Exhibitionism in Students - Nur Aini Hikmawati; Luh Putu Sri Lestari; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Postponement (Procrastination) is a behavior to postpone and continue to the next day, and in a certain period of time feel lazy to do activities. This study aims to describe whether the service of behavioral counseling theory with self-management techniques can reduce procrastination behavior in students, and whether the service of behavioral counseling theory with self-management techniques can reduce exhibition behavior in students. The population in this study were all students of class VIII A, B, C at MTs totaling 90 students. The procedure in this study used a quantitative experimental method with a quasi-experimental research design with a pretest-posttest control group design. The data in this study were collected using observation, interviews, and questionnaires. The data were analyzed using the MANOVA test with the SPSS Statistics 29 for mac application. The results of the data analysis showed that a sig. value of 0.001 <0.05 was obtained, so it can be concluded that H0 is rejected, which means that the implementation of behavioral counseling with self-management techniques simultaneously effectively reduces procrastination and exhibition behavior in students. This article suggests that teachers pay more attention to the behavior of students who have tendencies or characteristics of procrastination and exhibitionist behavior in students at school.